Student Loans or Taxes? Financing Reform in Chile - Alarcón, Mario; Joaquín Brunner, José (International Higher Education, 2025)
<h3 id="the-chilean-idea-to-transition-from-a-student-loan-system-to-a-progressive-graduate-tax-represents-a-significant-development-in-the-financing-of-higher-education-though-designed-to-reduce-student-debt-and-promote-equity-this-reform-prompts-concerns-regarding-institutional-autonomy-financial-sustainability-and-redistribution-of-costs-we-examine-the-implications-of-the-proposed-higher-education-fund-fes-situating-chiles-experience-within-the-context-of-global-debates-on-access-cost-and-quality-in-higher-education" data-pm-slice="1 1 []">The Chilean idea to transition from a student loan system to a progressive graduate tax represents a significant development in the financing of higher education. Though designed to reduce student debt and promote equity, this reform prompts concerns regarding institutional autonomy, financial sustainability, and redistribution of costs. We examine the implications of the proposed Higher Education Fund (FES), situating Chile’s experience within the context of global debates on access, cost, and quality in higher education.